COUNSELING NIGERIAN RETIREES FOR POLITICAL PARTICIPATION - Tambawal, Malami Umar (Sokoto Educational Review, 2020)
This paper discusses counseling Nigerian retirees for political participation. As one disengages from active public service he needs something to occupy his time so that he does not fall into psychological problems of retirement such as disbelief or denial, anxiety disorder, anger, depression and substance abuse. For those that chose political participation, certain counseling strategies need to be fulfilled for them to make a smooth transition from the work place to the political arena, which is completely a new field in one’s life. Behaviour modification theories, individual theory of Alfred Alder and Erickson personality theories were proffered as possible approaches by counselors while counseling retires for political participation.